Identification and Characterization of Arcanobacterium canis from Companion Animals in Germany and The United Kingdom - Siti Gusti Ningrum; Antonia Kreitlow; Christoph Lämmler; Ellen Prenger-Berninghoff; Christa Ewers; Geoffrey Foster; Madeleine Plötz; Amir Abdulmawjood (Progress in Microbes and Molecular Biology)
Arcanobacterium canis is a novel species of the Arcanobacterium most closely related to A. haemolyticum. This study aims to characterize two A. canis isolates recovered from companion animals, specifically the claw of a cat and a vaginal swab from a dog. This study used real-time PCR to characterize A. canis isolated from companion animals. Two isolates of A. canis were recovered from purulent material from the claw of an 11-year-old cat in Germany and a vaginal swab of a dog in the United Kingdom. The samples were characterized phenotypically and genotypically. Both isolates were analyzed using culture methods, biochemical analysis, MALDI-TOF MS, real-time PCR amplification and sequencing of the 16S rRNA gene, and rpoB, gap, and tuf genes. The findings showed that the isolates P5197-15 and M214-96-1 obtained from companion animals were successfully characterized and confirmed to species level by real-time PCR amplification and sequencing of the 16S rRNA gene, as well as the genes of rpoB, gap, and tuf. This study seeks to comprehensively understand the characteristics of A. canis isolates obtained from companion animals. Such knowledge is essential for accurate diagnosis, treatment, and control of infections caused by this pathogen in veterinary medicine. Additionally, it contributes to the broader understanding of the genetic diversity and characteristics of A. canis, which can have implications for public health and animal well-being.